Abigail [videorecording (Blu-Ray + DVD)] - Shields, Stephen, 1987-; Busick, Guy, 1975-; Barrera, Melissa, 1990-; Stevens, Dan, 1982-; Weir, Alisha; Newton, Kathryn, 1997-; Catlett, Will, 1982-; Durand, Kevin; Cloud, Angus, 1998-2023; Esposito, Giancarlo; Goode, Matthew, 1978-; Morton, Aaron; et al. (Universal, 2024)
After a group of would-be criminals kidnap the 12-year-old ballerina daughter of a powerful underworld figure, all they have to do to collect a $50 million ransom is watch the girl overnight. In an isolated mansion, the captors start to dwindle, one by one, and they discover, to their mounting horror, that they're locked inside with no normal little girl.